THE IMPACT OF FUNDING DECISIONS ON THE ECONOMIC ENTERPRISE VALUE - Ammar Benhimida (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to highlight the relationship between the financial structure decision of the examined enterprise and its contribution to enhancing its market value, specifically through analyzing the effect of financial leverage. The significance of this research lies in identifying the appropriate funding decision that will inevitably impact the enterprise’s present and future. The study concludes that the funding decision adopted by the examined enterprise has a negative effect on profitability ratios—specifically, as the volume of loans increases, profitability decreases. In other words, the effect of financial leverage is negative.